SYNTHESIS OF PILLARED CLAYS FOR USING THEM AS CARRIERS OF CATALYTIC SYSTEMS - K.A. Shorayeva; B.K. Massalimova; S.M. Nauryzkulova; Sadykov V.A. (Academic Scientific Journal of Chemistry, 2020)
. Natural clays are of particular interest for their rational use as not only adsorbents, but also carriers of new highly selective catalysts. This article presents an overview of the application of pillared clays in catalytic chemistry as catalyst matrix. The physicochemical properties of the synthesized Al-, Zr-, Al / Zr-modified clays were studied by BET, XRF and elemental analysis. The elemental composition of montmorillonite and kaolinite clays was determined. Pillared clays with high specific surface (montmorillonite clay from 20 to 243 m2 /g and kaolinite clay from 5 to 66 m2 /g.) were obtained. The use of pillared clays in catalysis will help to solve the problems of the development of domestic production of catalysts and the replacement of expensive imported analogues